2021
DOI: 10.1101/2021.09.08.459535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 triggers DNA damage response in Vero E6 cells

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus responsible for the current COVID-19 pandemic and has now infected more than 200 million people with more than 4 million deaths globally. Recent data suggest that symptoms and general malaise may continue long after the infection has ended in recovered patients, suggesting that SARS-CoV-2 infection has profound consequences in the host cells. Here we report that SARS-CoV-2 infection can trigger a DNA damage response (DDR) in African g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a study investigating the ability of SARS-CoV-2 infection to affect DNA damage response and telomere stability, it was reported that TRF2 expression was decreased in infected Vero E6 kidney cells. In the study, it was shown that decreased TRF2 expression destabilizes telomeres, initiates telomere fusions, and causes genomic instability 36 . The contributions of the Shelterin proteins TRF1 and TRF2 to the maintenance of genomic integrity and telomeric stability are invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the ability of SARS-CoV-2 infection to affect DNA damage response and telomere stability, it was reported that TRF2 expression was decreased in infected Vero E6 kidney cells. In the study, it was shown that decreased TRF2 expression destabilizes telomeres, initiates telomere fusions, and causes genomic instability 36 . The contributions of the Shelterin proteins TRF1 and TRF2 to the maintenance of genomic integrity and telomeric stability are invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some of the processes that we found signi cantly enriched among asymptomatic patients have been previously put in connection to SARS viral infection. For example, members of the machinery for DNA damage response have been shown to interact and affect the response to several DNA and RNA viruses (Lilley et al, 2007) and it has been recently demonstrated that these pathways are also triggered by SARS-CoV2 in vitro cellular models (Victor et al, 2021). The Fanconi anemia pathway is tightly linked to DNA repair processes involving homologous recombination and genome integrity (Michl et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some of the processes that we found significantly enriched among asymptomatic patients have been previously put in connection to SARS viral infection. For example, members of the machinery for DNA damage response have been shown to interact and affect the response to several DNA and RNA viruses 30 and it has been recently demonstrated that these pathways are also triggered by SARS-CoV-2 in vitro cellular models 31 . The Fanconi anemia pathway is tightly linked to DNA repair processes involving homologous recombination and genome integrity 32 .…”
Section: Respiratory or Thoracic Diseasementioning
confidence: 99%